2020
DOI: 10.29261/pakvetj/2019.122
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Cyclicity of Holstein-Friesian Crossbred Cows Shows Relation with Serum Biochemical Profiles during 45-60 Days Postpartum

Abstract: Reproductive performance of dairy cows is greatly affected by energy, protein and mineral profiles, which is also connected to postpartum anestrus. The present study was conducted during the period from December 2018 to May 2019 on 30 local x Holstein-Friesian crossbred lactating cows with parity 1-5 and body condition score of 2.0-3.5. This study aimed to compare serum glucose, cholesterol, triglycerides, total proteins, urea nitrogen, calcium, phosphorus and magnesium concentrations between anestrus and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(20 reference statements)
2
0
0
Order By: Relevance
“…These values suggested a low energy state that was likely influencing the development of the follicles, leading to follicular atresia and anestrus (Dhoble et al, 2004) [10] . Similar results were obtained by Uddin et al (2019) [11] , Agrawal et al (2015) [12] and Qureshi et al (2016) [13] in cattle. In line with the findings, Uddin et al (2019) [11] found that postpartum anestrus cows' serum glucose levels were significantly lower than those of regular cyclic cows.…”
Section: Glucose (Mg/dl)supporting
confidence: 88%
See 1 more Smart Citation
“…These values suggested a low energy state that was likely influencing the development of the follicles, leading to follicular atresia and anestrus (Dhoble et al, 2004) [10] . Similar results were obtained by Uddin et al (2019) [11] , Agrawal et al (2015) [12] and Qureshi et al (2016) [13] in cattle. In line with the findings, Uddin et al (2019) [11] found that postpartum anestrus cows' serum glucose levels were significantly lower than those of regular cyclic cows.…”
Section: Glucose (Mg/dl)supporting
confidence: 88%
“…Similar results were obtained by Uddin et al (2019) [11] , Agrawal et al (2015) [12] and Qureshi et al (2016) [13] in cattle. In line with the findings, Uddin et al (2019) [11] found that postpartum anestrus cows' serum glucose levels were significantly lower than those of regular cyclic cows. Comparably, Agrawal et al (2015) [12] found that postpartum anestrus cows had significantly lower mean serum glucose levels (42.58 ± 6.73 g/dl vs. 73.7 ± 10.69 g/dl) than cyclic cows.…”
Section: Glucose (Mg/dl)supporting
confidence: 88%